Avaliação da correlação entre o grau de displasia epitelial e o grau de infiltrado inflamatório em queilite actínica - Paiva, Marcos Antônio Farias de (2008)
Actinic cheilitis is considered a potentially malignant lesion caused by excessive ultraviolet and solar radiation exposition. It is believed that the inflammation presented in potentially malignant lesions acts like a defense mechanism, but in case of failure it promotes cellular changes from potentially malignant lesions to malignant lesions. The aim of the present study is to evaluate the correlation between inflammatory infiltration and the degree of epithelial dysplasia in actinic cheilitis. 25 cases of actinic cheilitis were selected from clinical charts of the Head and Neck Surgery Department of Dr. Napoleão Laureano Hospital. Glass slide histopathological evaluation was performed and epithelial and connective tissue alterations were determined. Descriptive statistical analysis, Pearson´s, chi-square and ANOVA test was applied, considering p<0,05. 56% of the total samples were men and 44% were women. The mean age was 58,9 ± 15,3 years. Actinic cheilitis lesions were more prevalent in the inferior lip (64%). 72% of the cases there were a degree of epithelial dysplasia. The moderate degree of dysplasia was more frequent (28%), 24% presented severe dysplasia and 20% mild dysplasia. All the cases presented any degree of inflammation, 36% mild inflammatory infiltration, 24% moderate and 40% intense. All cases presented solar elastosis. There was statistical significant correlation between the degree of dysplasia and the intensity of inflammatory infiltration, with p=0,001 ANOVA and chi-square with p=0,0030. The results of this study indicate that epithelial dysplasia was influenced by the presence and intensity of inflammatory infiltration.